Milking frequency, estradiol cypionate, and bST alters milk yield and reproductive outcomes in dairy cows - C.A. Blevins; J.J. Aberle; B.A. Hensley; S.M Tiffany (Kansas Agricultural Experiment Station Research Reports, 2002)
The objective of this study was to determine how milking frequency, estradiol cypionate (ECP) postpartum therapy given at 1 week after calving, and biweekly bovine somatotropin (bST) administration alter lactational and reproductive outcomes in dairy cattle. Holstein cows (n=144) were randomly assigned to eight treatments (18 cows per treatment): 1) twice daily milking frequency (2x), 10-mg injection of ECP at 1 week after calving (ECP), and bST (given biweekly according to label beginning in the ninth week of lactation); 2) 2x milked, oil (cottonseed oil vehicle for ECP), bST; 3) 2x milked, ECP, and no bST; 4) 2x milked, oil, and no bST; 5) four-times daily milking frequency (4x; first 30 days in milk then 2x thereafter), ECP, and bST; 6) 4x milked, oil, and bST; 7) 4x milked, ECP, and no bST; and 8) 4x milked, oil, and no bST. Milk yields were recorded at each milking during the first 90 days of lactation. Milk samples were collected weekly at each milking and composited to determine milk components (percentages of fat, protein, lactose, solids-not-fat [SNF], milk urea nitrogen [MUN], and somatic cell count [SCC]). Energy-corrected milk yields were calculated for the first 90 days and for whole lactation yields (305-2x- ME standardized lactation records). Ovulation before first AI was synchronized beginning between 59 and 72 DIM using 100 :g of GnRH given 7 days before 25 mg of PGF2", followed in 24 hr by 1 mg of ECP. Cows were inseminated after detected estrus or at 48 hr after ECP. Pregnancy rates were assessed by transrectal ultrasonography 28-30 days after AI. Postpartum ECP therapy increased milk production for first-lactation 2x cows, but decreased milk yields of the multiparous 4x cows until bST restored those yields. Pregnancy rates were greater for the 4x cows given the postpartum ECP therapy injection, despite fewer cows cycling before AI. In conclusion, postpartum ECP therapy increased pregnancy rates in 4x cows, but had a detrimental effect on milk yields of 4x milked cows unless bST was administered.; Dairy Day, 2002, Kansas State University, Manhattan, KS, 2002;
Keywords: Dairy Day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-121-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 898; Dairy; Estradiol cypionate; bST; Milking frequency; Fertility